Imperialism, industrialisation and war: the role of ideas in China's Japan policy, 1949-1965 - King, A (2012)
This thesis is a study of the People’s Republic of China’s foreign economic policy towards Japan between 1949 and 1965. In particular, the thesis explores Chinese policy-makers’ ideas about Japan in the wake of the War of Resistance against Japan (1937-1945), and considers how those ideas shaped China’s foreign economic policy towards Japan between 1949 and 1965. To do so, the thesis employs a four-part ideas framework that examines Chinese policy-makers’ background, foreground, cognitive and normative ideas about Japan, and shows how the interaction between these four different idea types shaped China’s Japan policy between 1949 and 1965. Furthermore, the thesis draws on over 200 recently declassified Chinese-language archival records from the Chinese Foreign Ministry, as well as additional Chinese, Japanese, US and British archival sources. It argues that China’s experience of Japanese imperialism, industrialisation and war during the first half of the twentieth century deeply shaped Chinese ideas about Japan after 1949, though in ways that at first seem counterintuitive. Although Japan had waged a brutal war against China, Chinese policy-makers viewed Japan as an important source of industrial goods, technology and expertise, and a symbol of a modern, industrialised nation-state. However, China’s experience of Japanese imperialism and militaristic aggression often made it difficult to justify the policy of ‘trading with the enemy’. Ultimately, the thesis argues that China sought to expand economic ties with Japan after 1949 because Chinese policy-makers believed that doing so would assist China in becoming a modern and industrialised state, one that was strong enough to withstand foreign imperialism and restore its central position in the international system. Chinese conceptions of Japan thus help to explain how Japan became China’s largest trade partner by 1965, despite the bitter legacy of the War of Resistance and the Cold War divide between the two countries after 1949.